WAKAF KORPORAT JOHOR CORPORATION DAN SUMBANGANNYA DALAM MEMENUHI TANGGUNGJAWAB SOSIAL ISLAM DI MALAYSIA: SATU TINJAUAN - Borham, Abd. Shakor; Mahamood, Siti Mashitoh (Journal of Techno-Social, 2013)
This paper will discuss the role of corporate waqf Johor Corporation (JCorp) and its contribution in fulfilling the Islamic social responsibility in Malaysia. As a government-owned corporations (GLCs), JCorp through its subsidiaries namely Waqaf An-Nur Corporation Berhad (WANCorp) is seen to have its own approach in contributing to society as a Islamic social responsibility in this country. Through waqf, JCorp not only managed to introduce a form of contemporary waqf, known as corporate waqf but was able to implement various welfare programs to the Muslim community through the profit dividend of units of donated exclusively. This study aims to review the extent to which the implementation of corporate waqf JCorp has contributed to the Muslim community as a socially responsible company in the country. To meet this goal, this study used two main research methods namely data collection methods and data analysis methods. The study found that in December 2010, totaling over RM3.6 million has been donated through implementation of waqf with three main programs as welfare and charity, human development, education and entrepreneurship capital, and special projects.The study concludes with several recommendations for improvements to strengthen the implementation of JCorp corporate waqf based on its great contribution to the Muslim community in Malaysia.